Ivan Leonidov: supposed realizations in Kislovodsk and Moscow - Zavadovsky, Petr (project baikal, 2021)
The article considers several realizations in Kislovodsk and Moscow in the second half of the 1930s. They have characteristics typical of Ivan Leonidov. The author speaks about the possibility and the degree of his participation as an author, as well as the arguments for this supposition.
Keywords: Ivan Leonidov; Sergo Ordzhonikidze Sanatorium; late constructivism